2023
DOI: 10.1038/s41586-023-06533-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of methyl-salicylate-mediated plant airborne defence

Qian Gong,
Yunjing Wang,
Linfang He
et al.

Abstract: This version of the article has been accepted for publication, after peer review (when applicable) and is subject to Springer Nature's AM terms of use (https://www.nature.com/nature-portfolio/editorial-policies/self-archiving-andlicense-to-publish#terms-for-use), but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections. The Version of Record is available online at: https://www.nature.com/articles/s41586-023-06533-3Use of the AM is subject to an embargo period (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…30 Moreover, a latest study pointed out that elevated levels of MeSA in aphid-infested tobacco plants can be perceived by neighboring plants' SABP2 and subsequently converted into SA. 37 In other words, SABP2 can convert exogenous MeSA into SA. Similarly, in this study, the FvMES2 gene expression level and the SA content in strawberries significantly increased after exogenous MeSA spraying, suggesting an active involvement of FvMES2 in facilitating the conversion of exogenous MeSA into SA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Moreover, a latest study pointed out that elevated levels of MeSA in aphid-infested tobacco plants can be perceived by neighboring plants' SABP2 and subsequently converted into SA. 37 In other words, SABP2 can convert exogenous MeSA into SA. Similarly, in this study, the FvMES2 gene expression level and the SA content in strawberries significantly increased after exogenous MeSA spraying, suggesting an active involvement of FvMES2 in facilitating the conversion of exogenous MeSA into SA.…”
Section: Discussionmentioning
confidence: 99%
“…SA Determination. The liquid chromatography−mass spectrometry (LC−MS) analysis to quantify SA content was performed as previously described, 37 with minor modifications. Briefly, strawberry fruit homogenate (100 mg) was subjected to 1:1 methanol/isopropanol extraction at −20 °C overnight.…”
Section: Heterologous Protein Purification and Enzyme Activity Assay ...mentioning
confidence: 99%
“…Additionally, the activity of cell wall hydrolysing enzymes is influenced by the natural cell wall configuration, which can be altered by high cell wall content and normal constituents in the middle lamella [ 54 ]. On the other hand, several reliable studies confirmed that the genetic factors and the function of the plant's defence system have a significant effect [ [55] , [56] , [57] ].…”
Section: Discussionmentioning
confidence: 99%
“…Aphids are one of the most serious agricultural and horticultural pests worldwide (Wang et al 2022;Jiang et al 2023;Gong et al 2023). They are phloem-feeding and cause extensive damage to the yield and quality of crops owing to their sap-sucking behavior and e cient transmission of numerous devastating viruses (Fereres and Moreno 2009;Zhang et al 2022).…”
Section: Introductionmentioning
confidence: 99%